2020
DOI: 10.36858/jkds.v8i2.232
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Tingkat Pengetahuan Pertolongan Pertama Pada Layperson Usia Anak Sekolah Terhadap Efikasi Diri Dalam Penanganan Kasus Cedera : a Systematic Review

Abstract: Cedera menjadi permasalahan serius yang memberikan dampak pada 4,7 juta orang di dunia. Angka cedera di Indonesia mencapai angka 9,2% dan salah satu kelompok rentan cedera adalah anak usia sekolah. Hal ini berhubungan dengan kondisi lingkungan yang tidak aman dan rendahnya kemampuan untuk melakukan tindakan pertolongan pertama. Untuk dapat melakukan tindakan yang tepat maka diperlukan keyakinan dan kepercayaan diri. Salah satu aspek penting yang berpengaruh pada efikasi diri adalah pengetahuan individu. Peneli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
2
0
2
Order By: Relevance
“…This makes it difficult for students to obtain training, and a lack of engagement in training is another reason that halts students from having appropriate abilities, preventing them from taking action on an object such as first aid for injuries. According to research (Nirmalasari N, et al, 2020) (Nastiti E M, et al, 2020), which found that the accuracy of first aid is critical in treating someone who has an injury or illness, particularly in the school setting. Students' understanding of first aid is critical for ensuring accuracy in the initial treatment of injuries.…”
Section: Discussionmentioning
confidence: 99%
“…This makes it difficult for students to obtain training, and a lack of engagement in training is another reason that halts students from having appropriate abilities, preventing them from taking action on an object such as first aid for injuries. According to research (Nirmalasari N, et al, 2020) (Nastiti E M, et al, 2020), which found that the accuracy of first aid is critical in treating someone who has an injury or illness, particularly in the school setting. Students' understanding of first aid is critical for ensuring accuracy in the initial treatment of injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Pencegahan dan pertolongan pertama pada cedera terutrama cedera ekstremitas sangat penting dilakukan di sekolah untuk menciptakan sekolah yang aman untuk anak-anak. (Nastiti, 2020).…”
Section: Pendahuluanunclassified
“…Pencegahan dan pertolongan pertama pada cedera terutama cedera muskuloskeletal sangat penting dilakukan di sekolah untuk menciptakan sekolah yang aman untuk anak-anak. (Nastiti & Darotin, 2022;Nastiti, 2020). Kegiatan ini dapat dimanfaatkan sebagai upaya pemberdayaan siswa untuk meningkatkan pengetahuan pertolongan pertama dalam membentuk siswa yang tangguh dalam memberi pertolongan kepada teman ataupun keluarga terutama pada kasus cedera muskuloskeletal seperti terkilir.…”
Section: Pendahuluanunclassified
“…Providing first aid is an important thing to do in the school environment considering that schools are locations with a high risk of extremity injuries. In addition, education is also needed to increase one's confidence before handling injuries (Nastiti, 2020).…”
Section: Introductionmentioning
confidence: 99%